Pendampingan Manajemen UMKM Melalui Program Bunda BISA Yatim Mandiri Mojokerto Untuk Meningkatkan Entrepreuner Skill - M. Soleh Mauludin; Zakiyatus Soimah; Latifatul Qolbi; Dhea Safina Imama; Sabila Putri Adilia; Azzara Al Dillah (LP3M IAIFA Kediri, 2025)
The Bunda BISA Program, organized by Yatim Mandiri Mojokerto, aims to enhance the skills and economic independence of widowed mothers who have lost their primary source of income. This program employs the Asset-Based Community Development (ABCD) method to develop business skills rooted in community assets. The assistance provided includes training in production skills, marketing, business management, and access to capital. The results of the program demonstrate a significant increase in the participants' entrepreneurial skills, understanding of marketing strategies, and self-confidence. Furthermore, progress in product packaging and business legality has enabled them to expand their market reach. However, challenges remain in digital marketing and product legality that require further optimization. The success of this program serves as a potential model for the economic empowerment of women in other regions.